(untitled) (Al-Academy, 2025)
In recent years, Saudi graffiti art has undergone a significant transformation, emerging as a contemporary phenomenon that reflects the cultural and artistic changes in Saudi Arabia. Based on this, the study aims to explore the aesthetics of the iconography of Saudi graffiti art by providing a theoretical framework on the concept of iconography and the features of contemporary Saudi graffiti art. Methodologically, the study employed Panofsky’s analytical approach on a purposive sample consisting of four graffiti works selected from the "Shift 22" festival and the "Rash for Mural Art" festival, both held in Riyadh between 2022 and 2023. The results demonstrated the feasibility of studying the aesthetics of Saudi graffiti art iconography using a methodology grounded in both theoretical and practical foundations. They revealed essential aesthetics that enhance cultural identity and national ambition through an inspiring and attractive visual style that conveys the Kingdom’s future vision. The study also offers recommendations for researchers to conduct in-depth studies that enhance cultural and artistic awareness of this art form, propose academic documentation of Saudi graffiti production, and support its development through organizing events and exhibitions at both local and global levels